Biphasic cortical macro‐ and microstructural changes in autosomal dominant Alzheimer's disease. Issue 4 (16th November 2020) - Montal, Victor; Vilaplana, Eduard; Pegueroles, Jordi; Bejanin, Alexandre; Alcolea, Daniel; Carmona‐Iragui, María; Clarimón, Jordi; Levin, Johannes; Cruchaga, Carlos; Graff‐Radford, Neill R.; Noble, James M.; Lee, Jae‐Hong; et al.
Abstract: INTRODUCTION: A biphasic model for brain structural changes in preclinical Alzheimer's disease (AD) could reconcile some conflicting and paradoxical findings in observational studies and anti‐amyloid clinical trials. METHODS: In this study we tested this model fitting linear versus quadratic trajectories and computed the timing of the inflection points vertexwise of cortical thickness and cortical diffusivity—a novel marker of cortical microstructure—changes in 389 participants from the Dominantly Inherited Alzheimer Network. RESULTS: In early preclinical AD, between 20 and 15 years before estimated symptom onset, we found increases in cortical thickness and decreases in cortical diffusivity followed by cortical thinning and cortical diffusivity increases in later preclinical and symptomatic stages. The inflection points 16 to 19 years before estimated symptom onset are in agreement with the start of tau biomarker alterations. DISCUSSION: These findings confirm a biphasic trajectory for brain structural changes and have direct implications when interpreting magnetic resonance imaging measures in preventive AD clinical trials.